Who gets referred for knee or hip replacement? A theoretical model of the potential impact of evidence-based referral thresholds using data from a retrospective review of clinic records from an English musculoskeletal referral hub - Andrew J Price; Andrew Judge; Alastair Gray; Rachael Gooberman-Hill; David Beard; Adrian Sayers; Rob Middleton; Stephanie Smith; Karen L Barker; David Murray; Sujin Kang; Elena Benedetto; et al. (BMJ Open)
Objectives To estimate the relationship between patient characteristics and referral decisions made by musculoskeletal hubs, and to assess the possible impact of an evidence-based referral tool.Design Retrospective analysis of medical records and decision tree model evaluating policy changes using local and national data.Setting One musculoskeletal interface clinic (hub) in England.Participants 922 adults aged ≥50 years referred by general practitioners with symptoms of knee or hip osteoarthritis.Interventions We assessed the current frequency and determinants of referrals from one hub and the change in referrals that would occur at this centre and nationally if evidence-based thresholds for referral (Oxford Knee and Hip Scores, OKS/OHS) were introduced.Main outcome measure OKS/OHS, referrals for surgical assessment, referrals for arthroplasty, costs and quality-adjusted life years.Results Of 110 patients with knee symptoms attending face-to-face hub consultations, 49 (45%) were referred for surgical assessment; the mean OKS for these 49 patients was 18 (range: 1–41). Of 101 hip patients, 36 (36%) were referred for surgical assessment (mean OHS: 21, range: 5–44). No patients referred for surgical assessment were above previously reported economic thresholds for OKS (43) or OHS (45). Setting thresholds of OKS ≤31 and OHS ≤35 might have resulted in an additional 22 knee referrals and 26 hip referrals in our cohort. Extrapolating hub results across England suggests a possible increase in referrals nationally, of around 13 000 additional knee replacements and 4500 additional hip replacements each year.Conclusions Musculoskeletal hubs currently consider OKS/OHS and other factors when making decisions about referral to secondary care for joint replacement. Those referred typically have low OHS/OKS, and introducing evidence-based OKS/OHS thresholds would prevent few inappropriate (high-functioning, low-pain) referrals. However, our findings suggest that some patients not currently referred could benefit from arthroplasty based on OKS/OHS. More research is required to explore other important patient characteristics currently influencing hub decisions.